Effectiveness of Individualized Physical and Breathing Exercise Programs for COPD Patients Among College Students: A Comparative Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In this study, the quantitative research technique will be used. Data was collected from 200 COPD patients using a method comparable to an experiment but with a control group that is not. All pulmonary functions in the experimental group were very significant, indicating that the therapy was successful for pulmonary function, in contrast to the group that served as a control, where there was no statistically significant relationship between FIV, PEFR, oxygen saturation, or BHT. Additionally, the treatment's impact on breathing exercises was examined, and the experimental group showed a very significant result. Scored 11.62 on the post-test and 5.6 on the Alternative Nostrils exercise. A extremely important ANE score was determined. The results of the diaphragmatic exercise were 11.9 on the post-test, up from 5.3 on the pre-test. Statistical analysis revealed a small but notable shift in the post-test treatment group's DE score. Purse lip exercise resulted in an increase from 5.08 on the pretest to 11.2 on the posttest. Significant improvements in the experimental group's purse lip exercise score were seen.